Molecular epidemiology of endemic Clostridioides difficile infection in Japan. (April 2022) - Senoh, Mitsutoshi; Kato, Haru
Abstract: We reviewed the molecular epidemiology of Clostridioides difficile infection (CDI) in Japan by reviewing articles in which typing analysis was performed on recovered C. difficile isolates. Most of the multicenter studies showed that the major prevalent PCR-ribotypes (RT018-related type, RT014, RT002, RT369, and RT017) accounted for more than 75% of clinical isolates in Japan, which has not changed significantly since the late 1990s. Within the RT018-related isolates, a shift from RT018 to RT018ʹʹ (QX239) and the persistence of high levels of antimicrobial resistance were observed. Among toxin A-negative, toxin B-positive C. difficile, RT017 was replaced by RT369, which was more resistant to fluoroquinolone. The isolation rate of binary toxin-positive isolates was low (2–6%), except in one study (10%). Isolation of RT027 and RT078 was rare in endemic settings, while there was a first report of a nosocomial outbreak due to RT027 C. difficile in 2019. Notably, the vast majority of RT027 isolates, including the epidemic strain responsible for the outbreak, were susceptible to moxifloxacin, suggesting that Japanese RT027 represents the pre-epidemic RT027 genetic background. To understand the CDI burden in Japan, a nationwide strain-based surveillance system is imperative. Highlights: C.difficile prevalent in Japan are RT018-related, RT014, RT002, RT369, and RT017. The prevalence of the major ribotypes has not significantly changed for decades. Within RT018-related type, a shift from RT018 to RT018ʹʹ (QX239) has occurred. In A − B + isolates, RT017 was replaced by RT369 with fluoroquinolone resistance.